PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA DAN UPAYANYA DALAM MENGHADAPI TANTANGAN ERA SOCIETY 5.0. - Nurul Dwi Lestari (Universitas Khairun, 2022)
This study aims to describe the problems of education and learning Indonesian as well as its efforts to face the challenges of the era of society 5.0. The specific objectives in this discussion are to describe the challenges of teaching the era of society 5.0 for each level of education, the needs of teaching Indonesian, and planning education and learning Indonesian to face the challenges of teaching in the era of society 5.0. The challenges of teaching Indonesian at every level are different, as are their needs. Therefore, efforts to overcome the problems of learning Indonesian must be adapted to the challenges and needs of each level of education. Keywords: problematic, education, learning, Indonesian language.